Oblicz:
a) 1 –  frac{1}{8} =
b) 2 –  frac{2}{3} =
c) 3 –  frac{3}{5} =
d) 1 –  frac{1}{2} =
e) 2 –  frac{1}{2} =
f) 1 –  frac{3}{5} =
g) 4 –  frac{3}{5} =
h) 1 –  frac{1}{9} =
i) 7 –  frac{1}{9} =
j) 3 –  frac{1}{2} =
k) 8 –  frac{3}{4} =
l) 10 –  frac{3}{7} =
m) 7 –  frac{1}{6} =
n) 5 –  frac{7}{10} =
o) 10 –  frac{2}{10} =

Gość:

a) 1 - 1/8= 7/8

b) 2 - 2/3 = 1,1/3

c) 3 - 3/5 = 2,2/5

d) 1 - 1/2= 1/2

e) 2 - 1/2 = 1,1/2

f) 1 - 3/5= 2/5

g) 4 - 3/5= 3,2/5

h) 1 - 1/9 = 8/9

i) 7 - 1/9= 6,8/9

j) 3 - 1/2= 2,1/2

k) 8 - 3/4= 7,1/3

l) 10 - 3/7= 9,4/7

m) 7 - 1/6= 6,5/6

n) 5 - 7/10= 4,3/10

o) 10 - 2/10=
9,8/10

Gość:

1 - 1/8 = 8/8 - 1/8 = 7/8
2 - 2/3 = 1 i 3/3 - 2/3 = 1 i 1/3
3 - 3/5 = 2 i 5/5 - 3/5 = 2 i 2/5
1 - 1/2 = 2/2 - 1/2 = 1/2
2 - 1/2 = 1 i 2/2 - 1/2 = 1 i 1/2
1 - 3/5 = 5/5 - 3/5 = 2/5
4 - 3/5 = 3 i 5/5 - 3/5 = 3 i 2/5
1 - 1/9 = 9/9 - 1/9 = 8/9
7 - 1/9 = 6 i 9/9 - 1/9 = 6 i 8/9
3 - 1/2 = 2 i 2/2 - 1/2 = 2 i 1/2
8 - 3/4 = 7 i 4/4 - 3/4 = 7 i 1/4
10 - 3/7 = 9 i 7/7 - 3/7 = 9 i 4/7
7 - 1/6 = 6 i 6/6 - 1/6 = 6 i 5/6
5 - 7/10 = 4 i 10/10 - 7/10 = 4 i 3/10
10 - 2/10 = 9 i 10/10 - 2/10 = 9 i 8/10

Dodaj komentarz


Powiązane pytania